EMPOWERING THE COMMUNITY AND CADRES FOR PROMOTIVE AND PREVENTIVE EFFORTS IN NON-SPECIFIC CHRONIC LOW BACK PAIN CONDITIONS - Sugiono; Noerdjanah (International Journal of Multidisciplinary Reseach, 2026)
Chronic nonspecific low back pain is a musculoskeletal problem that can interfere with physical activity and functional ability. Community empowerment is needed to improve knowledge and skills in implementing promotive and preventive efforts. This community service activity aims to improve the knowledge and skills of cadres and the community through education and core stability exercise training. The activity was carried out at the Elderly Posyandu (Integrated Health Post) in Tohudan Village, Colomadu District, Karanganyar Regency, Central Java. There were 30 participants, consisting of 8 cadres (26.7%) and 22 community members (73.3%). The activity was carried out through counseling using educational leaflets, demonstrations, core stability exercise practice with assistance, and strengthening the role of cadres. The results showed that all 30 participants participated in the activity and gained education and practical experience in preventing and reducing low back pain. Cadre involvement is essential to support the sustainability of training at the community level. Further evaluation using pre-post knowledge measurements and pain scores is needed to quantitatively measure the program's effectiveness.